P. granatum Peel Polysaccharides Ameliorate Imiquimod-Induced Psoriasis-Like Dermatitis in Mice via Suppression of NF-κB and STAT3 Pathways - Chen, Haiming; Wang, Cheng; Tang, Bin; Yu, Jingjie; Lu, Yue; Zhang, Junhong; Yan, Yuhong; Deng, Hao; Han, Ling; Li, Shaoping; Lu, Chuanjian (Frontiers in Pharmacology, 2022)
Psoriasis is a chronic and refractory inflammatory and autoimmune-mediated cutaneous disease affecting approximately 2%–3% of global population. Most of the current therapies could relieve symptoms rapidly, while the side effects cannot be negligible. Hence, it is urgent to explore much safer and more effective treatments. In the current work, we evaluated the potential beneficial effect of P. granatum peel polysaccharides (PPPs) in an imiquimod-elicited psoriasis-like mouse model and unraveled its mechanism of action. First of all, PPPs were isolated from P. granatum peels, and the molecular weight and monosaccharide analysis were determined. The results revealed that PPPs could significantly ameliorate psoriasis-like skin lesions and reduce the Psoriasis Area and Severity Index (PASI) scores and transepidermal water loss (TEWL). PPPs could also attenuate the expression of CD3 and Ki67 in psoriasis-like mouse skin and suppress the serum or skin levels of pro-inflammatory cytokines including TNF-α, IL-6 and IL-8. Moreover, PPPs were able to upregulate the mRNA and protein expressions of AQP3 and FLG in the skin of mice. In addition, PPPs could inhibit the NF-κB and STAT3 signaling pathways as well. Overall, these results indicated that PPPs ameliorated the symptoms of psoriasis through inhibition of inflammatory cytokines by suppressing NF-κB and STAT3 signaling pathways and improved skin barrier protection via enhancing AQP3 and FLG. These observations potentially contributed to providing theoretical and experimental evidence for the clinical application of PPPs in psoriasis.